A special feature of corporate income taxation in Portugal: the autonomous taxation of expenses. Issue 4 (10th July 2017) - Dinis, Ana; Martins, António; Lopes, Cidália Maria
Abstract : Purpose: The purpose of this paper is to discuss the following research questions: Is the Portuguese corporate income tax (CIT) losing its internal consistency by extending the autonomous taxation of expenses (ATE)? Are receipts derived from autonomous taxes so relevant that what began as an exception is gradually becoming a permanent feature of the income tax? Given the constitutional principle that corporate taxation should be fundamentally based on income, is the taxation of expenses unconstitutional? Is Portugal an international outlier, in applying this type of taxation to corporate expenses? Design/methodology/approach: The methodology used in the paper is a blend of legal research method and case study analysis. The interpretation of legal texts and the ratio legis discussion (hermeneutical side), the evaluation of advantages and disadvantages of autonomous taxes (argumentative approach) and the use of aggregate data to gauge an impression of autonomous taxes' impact on global tax receipts (empirical side) will, jointly, be used to analyse the topic. Autonomous taxation is a case study on how a (albeit distortive) solution is being applied in an European Union (EU) country to significantly enhance corporate-related tax revenue. Findings: The authors conclude that autonomous taxation is a relevant source of revenue and its elimination is not foreseeable, at least in the medium term. Moreover, the extension of the tax base is gradually transforming CIT in a kind of dual tax, by charging profits and some expenses. The Constitutional Court, stressing the equity principle, has not ruled autonomous taxation unconstitutional, invoking usefulness against tax evasion. Finally, with the exception of some Portuguese-speaking countries, no other comparable international experience is observed. Practical implications: The autonomous taxes (ATE) and its progressive enlargement imply, on the one hand, that the CIT has been slowly, but inexorably, losing its sole purpose of taxing profits, and imposing a tax penalty on an increasing set of accounting expenses. On the other hand, the growing number of expenses subjected to taxation leads some authors to ponder if the Portuguese tax regime is losing attractiveness. By increasing ATE's scope, the effective rate tends to move upwards, countering reductions in the statutory rate. Finally, tax law will increasingly influence managers' daily decisions, given the set of expenses targeted by autonomous taxes. Originality/value: Taking into account the aim of this study, the discussion of a Portuguese particular feature of corporate taxation can highlight useful policy points to a broader audience. Many Organization for Economic Cooperation and Development (OECD) countries face a dire situation in public finances. Therefore, given the pressure to increase tax receipts, the ATE can be a case study on how a (albeit distortive) solution is being applied in an EU country to significantly enhance corporate-related tax revenue.